Collective Narcissism and In-Group Satisfaction Predict Opposite Attitudes Toward Refugees via Attribution of Hostility - Dyduch-Hazar, Karolina; Mrozinski, Blazej; Golec de Zavala, Agnieszka (Frontiers in Psychology, 2019)
We examined whether and why collective narcissism (i.e., resentment for insufficient recognition of the in-group’s importance) versus in-group satisfaction (i.e., a belief that the in-group and one’s membership in it are reasons to be proud) have opposite, unique associations with hostility towards Syrian refugees in Poland. Results of two cross-sectional studies (Study 1, N=1066 and Study 2, N=419) converge to indicate that collective narcissism predicts hostility towards Syrian refugees via attributing Syrian refugees with hostile intentions towards Poles. In-group satisfaction is associated with rejection of hostile actions towards Syrian refugees because it decreases hostile attribution bias with regards to Syrian refugees. Thus, being a satisfied member of a national group promotes tolerance towards refugees, while collective narcissism is associated with blaming refugees for provoking the in-group’s hostility.